Impacto da salinidade na qualidade e conservação pós-colheita do maxixe (Cucumis anguria L.) - Morais, Divanovina Lais de (Brasil, 2017)
The gherkin is a vegetable of the family of the Cucurbitacea creeping plant or creeper, annual, rustic and cultivated in small scale. The commercial groups of these fruits, with and without aculeus, present a short shelf life. Its quality and productivity are influenced by the conditions of cultivation whose information is few in the literature. Thus, the purpose of this work was to evaluate the impact of salinity on quality and post-harvest conservation of gherkin. For this, an experiment was carried out in a randomized block design, with treatments arranged in a 2 x 4 factorial scheme (two cultivars, 'Gherkin do Norte' and ' Gherkin Liso Gibão' and four levels of salinity - 0.50; 2.0, 3.5 and 5.0 dS m-1), with three replicates, the experimental unit being represented by six plastic vessels with a capacity of 10 liters of substrate, with one plant in each vessel. The harvest was carried out 60 days after planting of the seedlings and the following analyzes were carried out: length, fruit diameter; soluble solids; titratable acidity; SS/AT ratio; total sugars; chlorophyll and total phenolics. The Maxixe 'Liso Gibão' presented higher production and the fruits were stored at 15 ° C and 85% RH for 0, 3 and 6 days. The use of saline solution reduced the fruit length and diameter and increased pH, soluble solids and SS / AT ratio. The cultivar 'Liso Gibão' was superior to 'North' cultivar for the variables length, diameter, pH, total sugars and SS/AT ratio. The Liso Gibão fruits were stored during six days without loss of quality. Fruits cultivated with saline solution of 2.0 dS m-1 presented higher acidity and chlorophyll during storage, but reduced total sugars and pH in fruits of gherkin
Impact of salinity on quality and post-harvest conservation of maxixe (Cucumis anguria L.)
Keywords: Clorofila; Fenólicos; Maxixe do Norte; Liso Gibão; Chlorophyll; Phenolics; Gherkin do Norte; Liso Gibão; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA